Program Pemberdayaan Masyarakat Surodadi: Pengelolaan Sampah Organik Menjadi Pupuk Kompos dengan Metode Composting Bag - Nurfaiz, Wildan Muhammad; Maulana, Muhammad Adiv Azhar; Mustofa, Hawin Alawiyah; Thora, Reyhan Edgarda; Ardiansyah, Faisal; Nisa, Rizka Melfyanti Khoirun; Maharani, Rosita; Febriyanti, Meliana; Anggraeni, Vena; Hafiza, Vanida Nurul; Wijayanti, Septi Nur (Universitas Muhammadiyah Yogyakarta, 2025)
This community empowerment program aims to raise awareness among the residents of Padukuhan Surodadi, Donokerto Village, regarding organic waste management through education and hands-on composting practices using the composting bag method. The main issue faced by the community is the management of household organic waste, which, if not properly handled, can lead to environmental pollution. The program was implemented through educational sessions and direct composting practice. The materials presented covered topics such as the environmental impact of waste, types of organic waste, and how to convert organic waste into compost fertilizer. During the practical sessions, community members were taught how to make compost using the composting bag method and engaged in discussions about potential challenges that may arise during the composting process. As a result of the program, more than 65% of household organic waste was successfully converted into compost. It is hoped that this initiative will continue to be developed by the community, eventually enabling the reduction of 100% of household organic waste while simultaneously improving soil fertility and overall environmental quality